Perlawanan Penyintas Body Shaming Melalui Media Sosial - Micheal Micheal; Suzy S. Azeharie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
As the era progresses, technological advances bring ease in accessing information from various media, one of which is social media. One of the most popular social media is Instagram. Instagram is a social media that allows their users to share information in the form of images, videos or writings. But social media is often used as a means to mock individuals with the action of body shaming. Body shaming is an act of commenting on all aspects of one's body. Body shaming action occurs due to the ideal body standardization. The ideal body standardization differs from one place and culture, more often experienced by women. However some people resist the actions of body shaming experienced. Some body shaming survivors have courage to resist such an act by direct or social media resistance. The purpose of this research is to find out the form of resistance by the survivors of body shaming through Instagram. The study uses phenomenological research methods with qualitative descriptive approach. Research data is derived from depth interviews on five interviewees, observations, document studies and literature studies. The conclusion is the form of resistance of the survivors of body shaming through social media Instagram divided into two, open resistance and closed resistance. Adapted to the characteristics of body shaming survivors. The open resistance is characterized by an open interaction between the Group One and the other group. While hidden resistance is characterized by a closed interaction, indirect inter-group. Seiring perkembangan zaman, kemajuan teknologi menghadirkan kemudahan dalam mengakses informasi dari berbagai media, salah satunya media sosial. Salah satu media sosial yang digemari adalah Instagram. Instagram merupakan media sosial yang memungkinkan penggunanya untuk berbagi informasi dalam bentuk gambar, video maupun tulisan. Namun, media sosial kerap dijadikan sarana untuk mengejek individu dengan tindakan body shaming. Body shaming merupakan tindakan mengomentari segala aspek dalam tubuh seseorang. Tindakan body shaming terjadi karena standarisasi tubuh ideal. Standarisasi tubuh ideal berbeda-beda tergantung dari tempat dan budaya dan lebih sering dialami oleh perempuan. Namun, beberapa orang melawan dari tindakan body shaming yang dialami dan mereka disebut dengan penyintas. Beberapa penyintas body shaming berani melakukan tindakan perlawanan secara langsung maupun melalui media sosial. Tujuan penelitian ini adalah untuk mengetahui bentuk perlawanan yang dilakukan oleh penyintas body shaming melalui Instagram. Penelitian ini menggunakan metode fenomenologi dengan pendekatan deskriptif kualitatif. Data penelitian diperoleh dari wawancara mendalam, pengamatan langsung, studi dokumen dan studi kepustakaan. Kesimpulan penelitian ini adalah bentuk perlawanan penyintas body shaming melalui media sosial Instagram terbagi menjadi dua, yaitu bentuk perlawanan terbuka dan bentuk perlawanan tertutup disesuaikan dengan karakteristik penyintas body shaming. Perlawanan terbuka dikarakteristikkan dengan adanya interaksi terbuka antara kelompok satu dengan kelompok lainnya. Sementara perlawanan tersembunyi ditandai dengan adanya interaksi tertutup atau tidak langsung antar kelompok